Swearing in English among a group of female Malaysian teenagers - Baudin, Nurliyana; Paramasivam, Shamala (2014)
Swearing among teenagers in the Malaysian setting is becoming normal although the Malaysian culture generally frowns on swearing. This societal phenomenon is understudied in the context of Malaysia and little is known about why teenagers swear, the kinds of swear words used, and their viewpoints of swearing. The present study was conducted on 51 female teenagers in Malaysia to investigate their swearing behaviour in English. Data was collected using a questionnaire and interviews were conducted to triangulate the findings of the questionnaire. The study showed that Malaysian female teenagers swear regularly using their favourite swearwords,shit, damn, and hellfollowedby bitch, fuck and bullshit. The findings show that swearing functions as a tool to deal with daily life affairs: firstly, to let off steam when experiencing negative emotions mainly anger and frustration, and secondly, to display solidarity when joking and storytelling with friends. The study shows they swear amongst themselves as girlfriends, rarely with their male friends and strangers, and seldom with parents and teachers.